Global availability of antivenoms: the relevance of public manufacturing laboratories - Gutiérrez, José María (2018)
Snakebite envenoming is a serious global public health problem, and international initiatives, under the coordination of the World Health Organization and its regional offices, are being developed to reduce the impact of this neglected tropical disease. The global availability of safe and effective antivenoms is one of the key aspects in this global strategy. This review discusses the role of public antivenom manufacturing laboratories for ensuring the supply of antivenoms. The difficulties faced by public laboratories are discussed, together with some tasks that need to be implemented for strengthening them. In addition, the concept of ‘redundancy’ in the supply of antivenoms is emphasized, as a way to cope with the risks associated with the provision of antivenoms by few manufacturers. In general, the public sector should play a leading role, in antivenom availability and other aspects as well, within the global struggle to reduce the mortality and morbidity caused by snakebite envenoming.